Systematic Review on Sharia Supervisory Board in Islamic Banking - Nadiyah Mu’adzah (SMART Insight, 2022)
This study aims to determine previous research trends on Sharia Supervisory Board (SSB), assess the relationship of research collaboration, and identify future research directions. It uses 147 Scopus articles regarding to sharia supervisory board that were published between 2004 and 2023, using a Bibliometric method and Systematic Literature Review (SLR). The data that has been collected for this study is processed using VosViewers software to produce results that can be analyzed. It is known that four sub-themes dominate the research related to the sharia supervisory board: the relationship between SSB to sharia banking performance, sharia financial management, sharia governance compliance, and sharia audit effectiveness. This study can be used as a guide for determining influential writers, journals, organizations, and countries, making it simpler for future scholars to locate sources that had a substantial influence on the growth of the sharia supervisory board literature. This result may also have implications for regulators to re-evaluate the effectiveness of the structure and performance of the SSB to control and oversee Islamic bank governance. It is hoped that researchers, practitioners and regulators will collaborate to improve the sharia supervisory board's quality in both theory and practice.